Historical novel in Egypt in the first third of the ХХ century - Koptileuova D Т (Journal of Oriental Studies, 2016)
In the second half of the 20-30-ies of XX century in the Egyptian historical novel is planned formation of a new, patriotic. Getting him to put such novelists as Ali al-Jary, Farid Abu Hadid, Mohammed Saeed al-Arya, Baksir Ali Ahmed, Abd al-Hamid al-al-Sahhar Hood, Adil Kamil. Continuing educational mortgaged historical novel tradition of cultivating the culture of the historical knowledge of the works of novelists carry and call for national independence, embodied in the image of the heroic past.